Material Turns of the Screw: The Collier’s Weekly Serialization of The Turn of the Screw (1898) - Kirsten MacLeod (Cahiers Victoriens et Edouardiens)
This essay considers the original Collier’s Weekly serialization of Henry James’s The Turn of the Screw (1898) from a materialist and sociological perspective. It uses the contexts of the magazine and contemporary literary culture together with an analysis of relevant periodical codes to consider the following: first, what did this story mean, in a broad sense, for a new, young editor attempting to reinvent a struggling magazine, and how did it contribute to creating a new meaning for Collier’s? Second, what did this story mean to James at this point in his career and in its Collier’s manifestation? Finally, how might readers of Collier’s have understood the tale, taking into account their understanding of the contemporary literary and periodical scene, James’s place in it, and the manner in which the story was presented in Collier’s? In considering these questions, this essay engages with existing scholarship on the Collier’s serialization but also with issues raised in the wider field of study on James and periodicals and with broader controversies about The Turn of the Screw itself. Specifically, it redresses oversimplified accounts of Collier’s as a publication in this period and assumptions that the magazine serial form produced unsophisticated readings of the story.